A Proposal for Risk Assessment of Low-Frequency Noise in the Human–Machine–Environment System - Michaela Balážiková; Hana Pačaiová; Marianna Tomašková (Applied Sciences, 2023)
Low-frequency noise, the frequency range from approximately 10 Hz to 200 Hz, has been recognized as a special environmental noise problem. The World Health Organization recognizes the special place of low-frequency noise as an environmental problem. Noise can damage hearing, and it affects the whole body. Low-frequency sound is heard by humans, but infrasound is not audible. Low-frequency sound is most often measured based on a weighting function of the frequency. The A-weighted level underestimates the effects of low-frequency noise. For the detrimental effects of low-frequency sound, it would be appropriate to apply measurements using Z-weighting. The aim of this paper was to propose a comprehensive method of acoustic risk assessment (CMARA) that implements the effects of low-frequency values of noise exposure. The proposed methodology has been applied in practice at four workplaces for seven work activities. A risk assessment using the proposed CMARA method for individual activities shows that the noise exposure time may pose a health risk in the occupational and environmental process due to exposure to low-frequency noise at the limit of audibility. A high risk was assessed for activities WA2 (machining) and WA3 (spot welding). This paper highlights the need to measure low-frequency noise using Z-filter weighting.